FROZEN SEMEN CHARACTERISTICS OF BALI BULL IN DIFFERENT AGE GROUPS - Witri, Brilla Widya; Arifiantini, Iis; Prasetyaningtyas, Wahono Esthi; Karja, Ni Wayan Kurniani (BRIN - Badan Riset dan Inovasi Nasional, 2025)
One factor that affects frozen semen characteristics is bull age. Increasing age induces changes in sperm that reduce frozen semen quality. This study aimed to evaluate the frozen semen characteristics of Bali bulls aged 3, 8, and 13 years. Frozen semen was derived from fresh semen with sperm motility > 70%. The frozen semen characteristics tested included motility, viability, plasma membrane integrity, acrosome integrity, and sperm abnormalities. Sperm motility was analyzed by computer-assisted sperm analysis (CASA). Viability was assessed using eosin-nigrosin staining; plasma membrane integrity was assessed using the hypoosmotic swelling test (HOST); acrosome integrity was assessed using Giemsa staining; and sperm abnormalities were assessed using Williams staining. The plasma membrane integrity of the 13-year-old group was significantly lower (P < 0.05) than that of the younger age groups. However, there were no significant differences (P > 0.05) in the other parameters. We conclude that age affects the integrity of the sperm plasma membrane in frozen semen from Bali bulls.